Plant-derived vesicles: isolation strategies and therapeutic applications - Li, Jiazhong; Wang, Zhiyi; Wang, Feiran; Du, Xiuwei; Pang, Xiaogang (Frontiers in Plant Science, 2026)
Plant-derived vesicles (PDVs) are vesicle-like structures secreted by plant cells, containing components such as membrane proteins、nucleic acids and enzymes. These vesicles play significant roles in plant growth, tissue repair and self-defense. Additionally, PDVs are safe and easy to extract, and they demonstrate promising therapeutic effects on inflammation, cancer and wound healing. Due to their unique properties, PDVs can serve as drug carriers, effectively shuttling through cells to aid disease treatment. In this study, we review the methods for separating and preparing PDVs and highlight their application in disease treatment using nanovesicles derived from plants such as cucumber、broccoli、lemon、turmeric、ginseng、ginger、garlic、grape、yam、tomato and grapefruit. The biomedical applications of PDVs in drug delivery, anticancer therapies, anti-inflammatory responses, antioxidation and wound healing are also introduced. Finally, the feasibility, characteristics, challenges and future prospects of PDVs are discussed.